2009
DOI: 10.1177/0363546509332816
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Suture Material and Knot Type

Abstract: The SMC knot using MaxBraid provides the strongest knot/suture combination of knots and sutures tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 38 publications
(99 reference statements)
2
65
0
6
Order By: Relevance
“…Although there are no universal conclusions regarding the suture with the best repair characteristics, braided polyester sutures often have shown higher load to failure than alternative choices [2,9,10]. Abbi et al [1] reported that knots tied with FiberWire 1 had the highest load to failure values, averaging 275.97 N. Swan et al [11] also looked at the effect of suture type on load to failure using Force Fiber TM , FiberWire 1 , and Ethibond Excel TM . Swan et al [11] observed the highest load to failure using Force Fiber TM suture across all three knots tested in their trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no universal conclusions regarding the suture with the best repair characteristics, braided polyester sutures often have shown higher load to failure than alternative choices [2,9,10]. Abbi et al [1] reported that knots tied with FiberWire 1 had the highest load to failure values, averaging 275.97 N. Swan et al [11] also looked at the effect of suture type on load to failure using Force Fiber TM , FiberWire 1 , and Ethibond Excel TM . Swan et al [11] observed the highest load to failure using Force Fiber TM suture across all three knots tested in their trial.…”
Section: Discussionmentioning
confidence: 99%
“…Abbi et al [1] reported that knots tied with FiberWire 1 had the highest load to failure values, averaging 275.97 N. Swan et al [11] also looked at the effect of suture type on load to failure using Force Fiber TM , FiberWire 1 , and Ethibond Excel TM . Swan et al [11] observed the highest load to failure using Force Fiber TM suture across all three knots tested in their trial. They observed a similar magnitude load to failure for their surgeon's knot tied with Force Fiber TM (230.1 N) as we observed for a racking hitch with one half hitch (273.2 N).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the nondegradable polyester sutures tested (Ethibond), which are the most commonly used sutures for rotator cuff repair, 25 supported the best cell survival and growth in vitro. Microscopy images showed excellent cell morphology and alignment on Ethibond.…”
Section: 24mentioning
confidence: 99%
“…5 In the search for the optimal arthroscopic knot, a number of biomechanical studies have evaluated different knot configurations and suture materials. 2,3,[12][13][14]17 Although there is no consensus regarding the ideal knot configuration or suture material, basic knot-tying principles have been identified that improve knot and loop security. Reversing the direction of half-hitches and switching the post limb between throws each increase knot security by increasing friction and internal interference.…”
mentioning
confidence: 99%